Effect of biofilm-hybrid mixing ratio and incubation time on tomato fruit quality parameter coated with MLECB - Ohale, Nonye Jennifer; Menkiti, Matthew Chukwudi; Okey-Onyesolu, Chinenye Faith; Ohale, Paschal Enyinnaya Ohale (CV. Strata Persada Academia, 2024)
The purpose of the study was to determine how well moringa oleifera leaf extracts and chitosan edible bio-preservative (MLECB) extended the shelf life of fresh tomato fruits. The existence of imines (C=N) at 1661.8 cm-1, as shown by functional group analysis, confirmed the cross-linking reaction between the -NH2 of chitosan and the carbonyl groups of MLE. Gas chromatography mass spectrometry (GC-MS) hydrocarbon and phytochemical investigation revealed that MLE contains a high concentration of antimicrobial hydrocarbons (Pentadecane = 18.46%; Tridecane = 12.386%; Heptacosane = 12.013 %). In a similar vein, it was discovered that MLECB included notable antioxidants, such as quercetin (10.265%). Following a 20-day period of non-refrigerated storage at 1% chitosan content and a 40:60 MLECB ratio, the tomato fruit retained a 2.1706 g/kg titratable acidity (TA) and a 20.01% decrease in weight loss.